Pedicle Descemet membrane endothelial keratoplasty performed using a new corneal punch. Issue 7 (July 2020) - Bala, Chandra
Abstract : The tail of a pedicle Descemet membrane endothelial keratoplasty (DMEK) graft was used to orient, center, and unroll a DMEK scroll and was safely truncated at the end of the surgery. Abstract : Purpose: To create a Descemet membrane endothelial keratoplasty (DMEK) graft with a pedicle that allows better control of orientation, centration, and unrolling of the DMEK scroll. Setting: Macquarie University Hospital, Sydney, NSW, Australia. Design: Prospective nonrandomized interventional case series. Methods: Eleven eyes of 10 patients with corneal endothelial failure underwent the modified DMEK surgery. A new corneal punch with a 7.5 mm central zone and a 3.0 mm long pedicle was used to produce a graft with a tail. The pedicle was used to orient and drag the graft into the anterior chamber, and the tail was extravasated. The graft was unrolled and centered using the pedicle, and 24% SF6 gas was injected to applanate the graft. The pedicle was truncated. The graft manipulation time, defined as the time from graft insertion to gas injection, was measured. The patient and donor characteristics, postoperative corrected distance visual acuity (CDVA), and endothelial cell count (ECC) at 3 months were reported. Results: Ten grafts attached with 1 requiring reinjection of gas. The CDVA improved to ≥6/9 in 9 eyes, and the remaining were limited by preexisting disease. The ECC loss for the first 5 grafts was 28% ± 5% with manipulation time of 12 ± 6 minutes. This improved to 18% ± 7% ( P = .03) and 3 ± 2 minutes ( P = .007) for the last 6 grafts. Conclusions: The new corneal punch generated a keyhole-shaped DMEK graft. After a period of learning, the manipulation time was decreased, improving ECC. The pedicle seemed to improve control over orientation, unrolling, centration, and rebubbling, potentially increasing the ease of DMEK surgery. The pedicle was safely truncated without sequelae.